Increased IL-26 associates with markers of hyperinflammation and tissue damage in patients with acute COVID-19 - Cardenas, Eduardo I.; Ekstedt, Sandra; Piersiala, Krzysztof; Petro, Marianne; Karlsson, Agneta; Kågedal, Åsa; Kumlien Georén, Susanna; Cardell, Lars-Olaf; Lindén, Anders (Frontiers in Immunology, 2022)
Interleukin-26 (IL-26) is released by several immune and structural cells following stimulation of toll-like receptors (TLRs), whereupon it can directly inhibit viral replication and enhance neutrophil chemotaxis. Given these unique properties, IL-26 has emerged as an intriguing mediator of host defense in the lungs. However, the role of IL-26 in COVID-19 has not been thoroughly investigated. Here, we characterized the involvement of IL-26 in the hyperinflammation and tissue damage that occurs in patients with acute COVID-19. We found that IL-26 is markedly increased in blood samples from these patients, and that the concentration of IL-26 correlates with those of the neutrophil-mobilizing cytokines IL-6, IL-8, and TNFα, respectively. Moreover, the increase in blood IL-26 correlates with enhanced surface expression of the “don’t eat me” signal CD47 on blood neutrophils isolated from patients with acute COVID-19. Finally, we found that the blood concentration of IL-26 correlates with that of increased lactate dehydrogenase, an established marker of tissue damage, and decreased mean corpuscular hemoglobin (MCH), a previously verified hematological aberration in COVID-19, both of which are associated with severe disease. Thus, our findings indicate that increased systemic IL-26 associates with markers of hyperinflammation and tissue damage in patients with acute COVID-19, thereby forwarding the kinocidin IL-26 as a potential target for diagnosis, monitoring, and therapy in this deadly disease.